2017
DOI: 10.17265/2159-5836/2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Achievement Emotions, Motivation and Language Learning Strategies of High, Mid and Low English Language Achievers

Abstract: Overseas research has shown that achievement emotions have direct relationships with "achievement outcome" and "achievement activities". The purpose of the present study aimed to compare the relationships between achievement emotions, motivation, and language learning strategies of high, mid and low achievers in English language learning at an international university in a southern province in China. Quantitative data were collected through a questionnaire survey of 74 (16 males, 58 females) TESL major studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
2
4
1
Order By: Relevance
“…Interestingly, regarding females, although prior research in Argentina (Sánchez Rosas, 2015), Turkey (Yükselir & Harputlu, 2014), and China (Tan, 2017) revealed that they experienced negative AEs more frequently, this study of Mexican females did not. One plausible explanation is that, in this study, positive AEs were higher across the board.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Interestingly, regarding females, although prior research in Argentina (Sánchez Rosas, 2015), Turkey (Yükselir & Harputlu, 2014), and China (Tan, 2017) revealed that they experienced negative AEs more frequently, this study of Mexican females did not. One plausible explanation is that, in this study, positive AEs were higher across the board.…”
Section: Discussioncontrasting
confidence: 79%
“…These studies focused on learning-related emotions, not those associated with testing. Tan (2017) found that Chinese university students reported more positive than negative AEs. Yükselir and Harputlu (2014) used the AEQ with Turkish university EFL learners and discovered that males reported more pride and enjoyment, and females more anxiety and shame.…”
Section: Aeq and Gender Differences When L2 Learningmentioning
confidence: 98%
“…On the one hand, this finding provides empirical evidence for the resource limitation theory [43] in thatan individual's cognitive resources are limited, and high-arousal boredom would occupy part of cognitive resources, thereby reducing his or her application of cognitive strategies (e.g., elaboration strategies) in the learning context. On the other hand, this finding is consistent with some previous studies [4] and inconsistent with others [44]. Previous studies have found a negative correlation between academic boredom and learning strategies [4,44].…”
Section: Discussionsupporting
confidence: 89%
“…Agreat number of studies have been designed to explore the antecedents and consequences of achievement emotions [2,3], which had beneficial implications for both educational intervention and teaching behavior strategies. Moreover, existing studies have verified the significant correlation between achievement emotion and learning strategies [4] and the correlation between learning strategies and academic proficiency [5]. However, the possible mediating effect of learning strategies between achievement emotions and academic proficiency was seldom studied from a quantitative approach, especially in the domain of EFL education.…”
Section: Introductionmentioning
confidence: 99%
“…Highly successful students have stronger internal learning motivations, and they use more effective language learning strategies and experience more positive feelings. Still, the students with low success have stronger external learning motivation, use more effective language learning strategies, and get more negative feelings (Tan, 2016). MacIntyre and Vincze (2017) examined the effect of positive and negative emotions on learning a second language in their study.…”
mentioning
confidence: 99%